MODIFIABLE RISK FACTORS FOR CHRONIC NONCOMMUNICABLE DISEASES AND THEIR CORRECTION IN CITIZENS DURING CLINICAL EXAMINATION OF THE ADULT POPULATION IN THE CITY POLYCLINIC IN 2025 - Saksena Ishita; E.I. Demina; E.V. Krug (MEDICUS, 2026)
The article discusses the issues of medical examination of certain groups of the adult population in the city clinic. The objective was to identify modifiable risk factors in patients and prioritize lifestyle modifications for preventive risk factor management counseling. Identification of risk factors was carried out in citizens of working age and older than working age. All necessary studies were carried out in accordance with the order of the Ministry of Health of the Russian Federation No. 404n, 2021, depending on the age of the patient. The most common risk factors in both groups were poor diet, low physical activity and overweight. Upon completion of the clinical examination, all patients received preventive counseling from a therapist to level risk factors with an emphasis on rationalization of nutrition and an increase in motor mode.